Longitudinal Structural MRI Findings in Individuals at Genetic and Clinical High Risk for Psychosis: A Systematic Review - Merritt, Kate; Luque Laguna, Pedro; Irfan, Ayela; David, Anthony S. (Frontiers in Psychiatry, 2021)
Background: Several cross-sectional studies report brain structure differences between healthy volunteers and subjects at genetic or clinical high risk of developing schizophrenia. However, longitudinal studies are important to determine whether altered trajectories of brain development precede psychosis onset. Methods: We conducted a systematic review to determine if brain trajectories differ between i) those with psychotic experiences (PE), genetic (GHR) or clinical high risk (CHR), compared to healthy volunteers, and ii) those who transition to psychosis compared to those who do not. Results: 38 studies measured grey matter and 18 studies measured white matter in 2473 high risk subjects and 990 healthy volunteers. GHR, CHR and PE subjects show an accelerated decline in grey matter primarily in temporal, and also frontal, cingulate and parietal cortex. In those who remain symptomatic or transition to psychosis, grey matter loss is more pronounced in these brain regions. White matter volume and fractional anisotropy, which typically increase until early adulthood, did not change or reduced in high risk subjects in the cingulum, thalamic radiation, cerebellum, retrolenticular part of internal capsule, and hippocampal–thalamic tracts. In those who transition, white matter volume and fractional anisotropy reduced over time in the inferior and superior frontooccipital fasciculus, corpus callosum, anterior limb of the internal capsule, superior corona radiata and calcarine cortex. Conclusion: High risk subjects show deficits in white matter maturation and an accelerated decline in grey matter. Grey matter loss is more pronounced in those who transition to psychosis, but may normalise by early adulthood in remitters.